AODV-ECA: Energy-Efficient AODV Routing Protocol Using Cellular Automata in Wireless Sensor Network - Qin Yu; Zhihui Xiao; Ning An (Dianxin kexue)
Since the battery equipped wireless sensors have limited energy supply, conserving energy to extend the lifetime becomes the most important requirement in the wireless sensor network（WSN）. An AODV routing protocol, AODV-ECA, was proposed, based on cellular automata（CA）mechanism, which was sourced from the thoughts of automatic breeding in biology. AODV-ECA could reduce and balance energy consumption to prolong the network lifetime by means of switching nodes' states between sleeping and working. Finally, AODV-ECA to other energy-efficient routing protocols by NS2 simulator was simulated and evaluated.